Diseño e implementación de un modelo de inclusión laboral de personas con discapacidad intercultural leve y moderada en grupo KFC - Benavides Celleri, Felipe Roberto (2015)
People with disabilities have similar rights to others, this includes decent and fair treatment, and also the right to live independently and take part in our society. All of these lead to the general law of inclusion in all areas. The right to employment inclusion allows people with disabilities to have a decent job, as many of them are at the expense of their families with various needs that can’t be fulfilled, at the same time those needs will multiply in a personal or familiar manner, bringing several problems. Therefore we have established several policies towards this priority sector, not only nationally but also internationally to eradicate inequality conditions. Since 1998 an Act of the right of employment for disabled people was placed in the general law of labor in our country, which establishes a mandatory minimal percentage of people with disabilities in companies as the first step to create an inclusive culture. In Ecuador segregation towards disabled people, or people with special needs, is still remaining, marginalizing society. If there is an appropriate term for all vulnerable populations it should be disabled people or people with special needs and they should be given their rightful place as someone with limitations in certain activities. For society to work as one with people with disabilities, we must have a level of understanding of the constraints and be able to provide support for their development. Beginning with this issue, and following all the rules and laws, a tool for inclusion of people with mild and moderate intellectual disabilities was created, this being a step to take a responsible inclusion between intellectual and other types of disabilities. Intellectual disability is a complex social problem. Currently it has sought to give a concrete decision quite apart from all the theories that have been raised. Even in Latin America integration of people with intellectual disabilities has been reshaped despite their socioeconomic context. Ecuador has encouraged the development of job seeking sources reforming rules to enable access to education.